PENGARUH TOTAL ARUS KAS, KOMPONEN ARUS KAS DAN LABA AKUNTANSI TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Sri Wahyuningsih; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2020)
This study aims to analyze the effect of total cash flow, cash flow components and accounting profit on stock returns. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) with an observation period of 2017-2019. The sampling techniqu is purposive sampling, in order to obtain a sample of 61 manufacturing companies for the 2017-2019 period. Data analysis is multiple linear regression. The results showed that total cash flow, operating cash flow, investment cash flow, financing cash flow and accounting profit simultaneously had a significant effect on stock returns. Based on the partial test results, Total Cash Flow, Operating Cash Flow, Investment Cash Flow, Financing Cash Flow and Accounting Profit have a positive and significant effect on Stock Returns. This research contribute to signaling theory.Keywords : Total Cash Flow, Operating Activity Cash Flow, Investment Activity Cash Flow, Financing Activity Cash Flow, Stock Return.